Some Remarks Regarding the Phraseological Inventory from Petre Ispirescu and Ion Creangă’s Fairy Tales - Buzoianu-Ambrinoc, Elvira (Acta Universitatis Danubius. Communicatio, 2024)
In this article, I aim at characterizing the phraseological inventory both of Petre Ispirescu and of Ion Creangă, as it is used in their fairy tales and illustrating certain functions. At first sight, the amount of set phrases or idioms encountered in Creangă’s texts might seem superior to that of Ispirescu’s. This impression can be caused by Creangă’s richness of expressive procedures compared to Ispirescu’s linguistic possibilities. As I tried to prove, both writers possess, actually, almost the same phraseological inventory. In this regard, I chose to compare some fairy tales, published by Ispirescu and Creangă, fairy tales which have a similar plot and many common features in their structure and content.